Western Pacific Oceanic Heat Content: A Better Predictor of La Niña Than of El Niño. Issue 18 (22nd September 2018) - Planton, Yann; Vialard, Jérôme; Guilyardi, Eric; Lengaigne, Matthieu; Izumo, Takeshi
Abstract: The western equatorial Pacific oceanic heat content (warm water volume in the west or WWVw ) is the best El Niño–Southern Oscillation (ENSO) predictor beyond 1‐year lead. Using observations and selected Coupled Model Intercomparison Project Phase 5 simulations, we show that a discharged WWVw in boreal fall is a better predictor of La Niña than a recharged WWVw for El Niño 13 months later, both in terms of occurrence and amplitude. These results are robust when considering the heat content across the entire equatorial Pacific (WWV) at shorter lead times, including all Coupled Model Intercomparison Project Phase 5 models or excluding Niño‐Niña and Niña‐Niño phase transitions. Suggested mechanisms for this asymmetry include (1) the negatively skewed WWVw distribution with stronger discharges related to stronger wind stress anomalies during El Niño and (2) the stronger positive Bjerknes feedback loop during El Niño. The possible role of stronger subseasonal wind variations during El Niño is also discussed. Plain language summary: El Niño and La Niña have strong societal impacts at the global scale, especially large‐amplitude El Niño events like in 1982–1983, 1997–1998, and 2015–2016. It is hence important to identify early warning signals for the occurrence of El Niño/La Niña. The equatorial Pacific Ocean heat content is a well‐known predictor of El Niño/La Niña several seasons ahead. In this study, we show that negative heat content anomalies lead more systematically to La Niña events than positive heat content to El Niño events. We suggest that the enhanced predictability of La Niña relative to El Niño is due to larger negative heat content anomalies ahead of La Niña events and a more unstable (and hence less predictable) ocean‐atmosphere system during El Niño. Key Points: The western equatorial Pacific heat content is the best El Niño‐Southern Oscillation oceanic predictor beyond 1‐year lead This relation is asymmetrical: La Niña amplitude and occurrence is more predictable than that of El Niño Weak western Pacific heat content recharges, stronger air‐sea coupling, and atmospheric stochasticity contribute to this asymmetry